Level of Community Participation in Efforts to Reduce the Incidence of Diarrhea in Toddlers in Palu City - Sulaiman, Miftahul Haerati (Preventif : Jurnal Kesehatan Masyarakat, 2025)
Diarrheal disease remains a significant public health problem, especially in children under five in developing countries with limited access to clean water and proper sanitation. In Indonesia, especially in Palu City, the incidence of diarrhea among children under five is still high and is related to the low knowledge and practice of clean and healthy living in the community. This study aimed to describe the level of community participation in efforts to reduce the incidence of diarrhea in children under five in Palu City. The study used descriptive quantitative method and was conducted from September 2020 to May 2021 in eight health centers representing all areas of Palu City. The sample consisted of 138 mothers of children under five, selected using a multistage random sampling technique. Data were collected through a structured questionnaire and analyzed descriptively. The results showed that most mothers of children under five were rarely involved in diarrhea prevention activities, such as health counseling, giving time and energy, and disseminating education to the community. The level of participation in the eight health centers tends to be quite low, with variations between regions that show inequality. The low involvement of mothers of children under five is thought to be influenced by a lack of awareness, limited time due to multiple roles, and not optimal support and supervision from the Puskesmas. It is concluded that mothers' participation in diarrhea prevention is still not optimal, so it is necessary to strengthen community-based health programs that are participatory and appropriate to the social context in order to increase active involvement in diarrhea prevention efforts in children under five.